Methodological quality and risk of bias of systematic reviews about loading time of multiple dental implants in totally or partially edentulous patients: An umbrella systematic review - Clovis Marinho Carvalho Heiderich; Tamara Kerber Tedesco; Syrio Simão Netto; Rafael Celestino de Sousa; Sergio Allegrini Júnior; Fausto M. Mendes; Thais Gimenez (Elsevier, 2020)
Background: There are several systematic reviews of multiple implant loading techniques, but results are conflicting. Aim: To perform an umbrella review on methodological quality of systematic reviews about techniques for loading multiple dental implants. Material and methods: MEDLINE (PubMed) and Scopus were searched up to December 31, 2019. Unpublished literature was searched through OpenGray and references of included articles were manually verified. Eligibility criteria were: articles had to (1) be about multiple dental implants; (2) mention the moment of loading; (3) be a systematic review. Two independent reviewers participated in the entire process. Qualitative description of included studies as well as methodological quality measurement and risk of bias through AMSTAR and ROBIS were performed. Results: 21 reviews were included. Thirteen stated that there was a similarity between loading techniques, two did not affirm which one was more appropriate and six mentioned that conventional technique was better. Eight papers were classified as high risk of bias, twelve as low and one as uncertain risk. Conclusion: When evaluating only studies with a low risk of bias, there are no significant differences in implant loading time.